TAHLIL AKHTHO’ AN-NABR WA TANGHIM FI MUHADATSATI AL-THOLABAH AL-YAUMIYAH BI AL-LUGHAH AL-ARABIYAH: تحليل أخطاء النبر والتنغيم في محادثة الطلبة اليومية باللغة العربية - Syafni, Hafidhah (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Arabic requires proficiency in voice stress and intonation in conversation, but most students do not pay attention to this area and they are mistaken in the delivery of a sentence so that it makes a misunderstanding in comprehending the meaning of the conversation, which is why this discussion is proposed. The purpose of this article is to find out how students use voice stress and intonation in daily Arabic conversations, what mistakes occur during conversations, especially in the themes of